Can elevated concentrations of ALT and AST predict the risk of 'recurrence' of COVID-19?. (2020) - Chen, L. Z.; Lin, Z. H.; Chen, J.; Liu, S. S.; Shi, T.; Xin, Y. N.
Abstract: 'Recurrence' of coronavirus disease 2019 (COVID-19) has triggered numerous discussions of scholars at home and abroad. A total of 44 recurrent cases of COVID-19 and 32 control cases admitted from 11 February to 29 March 2020 to Guanggu Campus of Tongji Hospital affiliated to Tongji Medical College Huazhong University of Science and Technology were enrolled in this study. All the 44 recurrent cases were classified as mild to moderate when the patients were admitted for the second time. The gender and mean age in both cases (recurrent and control) were similar. At least one concomitant disease was observed in 52.27% recurrent cases and 34.38% control cases. The most prevalent comorbidity among them was hypertension. Fever and cough being the most prevalent clinical symptoms in both cases. On comparing both the cases, recurrent cases had markedly elevated concentrations of alanine aminotransferase (ALT) ( P = 0.020) and aspartate aminotransferase (AST) ( P = 0.007). Moreover, subgroup analysis showed mild to moderate abnormal concentrations of ALT and AST in recurrent cases. The elevated concentrations of ALT and AST may be recognised as predictive markers for the risk of 'recurrence' of COVID-19, which may provide insights into the prevention and control of COVID-19 in the future.